Microwave-assisted hydrothermal liquefaction of biomass model components and comparison with conventional heating. (1st October 2020) - Yang, Jie; He, Quan (Sophia); Niu, Haibo; Dalai, Ajay; Corscadden, Kenneth; Zhou, Ningning
Abstract: Microwave-assisted hydrothermal liquefaction (MW-HTL) is a promising technology for the production of biocrude from biomass that usually consists of saccharide, lipid, protein and lignin. A few attempts have been recently made to study the MW-HTL of biomass, however exploration on biocrude formation under MW irradiation presents a gap in the research. MW-HTL of biomass model components and their mixtures were carried out, and it was found that saccharide and lipid interacted synergistically to produce higher volumes of biocrude under MW irradiation, while the antagonistic interaction was observed for protein-lipid and lignin-lipid. The influence of microwave and conventional heating on the yield/quality of biocrude was also compared by HTL of model components (individual, binary, ternary and quaternary mixtures) and actual feedstocks. The results of this comparison revealed that the influence of heating method depends on the nature of feedstock, for instance, MW irradiation led to a lower biocrude yield for saccharide, comparable biocrude yield for protein and lignin, and higher biocrude yield for lipids than conventional heating. HTL of Chlorella sp. microalgae under MW irradiation produced more biocrude than conventional heating, but HTL of spent coffee grounds and sawdust was not affected by different heating methods. The heating method also had negligible influence on the chemical composition of the resulting biocrude. Principle component analysis of the vast dataset obtained in this study also suggested that the influence of the selected heating method was highly associated with the substrates, however there is no certain preference on one heating method over the other.